Cloning and mutation of chinese hamster ovary cell elongation factor (cej) of vibrio cholerae - Alan, Jaime Jacqueline Ja Yap (2005)
Cholera caused by toxigenic Vibrio cholerae is a major public health problem confronting developing countries, where outbreaks occur in a regular seasonal pattern and are particularly associated with poverty and poor sanitation. The disease is characterized by a devastating watery diarrhea which leads to rapid dehydration, and death occurs in 50 to 70% of untreated patients. Prophylactic vaccination for cholera was initially thought as a means of control programme. Although cholera vaccine strains have been constructed with all known toxin (El Tor hemolysin, CT, Zot, and Ace) genes deleted or inactivated, some volunteers fed with these strain still develop diarrhea probably due to the presence of cell- associated CHO cell- elongating factor, cef In this study we therefore, have tried to clone and mutate this cef gene with the hope of eliminating its residual diarrheagenic effect, thus the development of improved VCUSM2 and VCUSM4 vaccine candidates. Accordingly, the cef factor was amplified from wild type Vibrio cholerae which was subsequently cloned into a cloning vector, pTZ57R/T at Eco321 site. The cef gene in pTZ57R was digested with Psyl enzyme, to allowing insertional mutational ligation to occur at this site. The PCR amplified kan resistance gene cassette from pTOP02.1 was used to insertionally mutate the cef gene as well as a marker for selection fallowing transformation. The selected clones with kan marker were screened by PCR for confirmation and subsequently verified by DNA sequencing